IRON ENRICHMENTS IN HYDROTHERMAL PLUMES OVER THE EAST PACIFIC RISE - Hudson A.; Bender M.L.; Graham D.W. (My University, 1986)
Manganese, iron, and helium isotopes have been measured in samples taken near the crest of the East Pacific Rise at 19°S. Samples were enriched in Mn and in He isotopes, as is typical for waters of this area. Samples were also enriched in Fe; Fe enrichments covary with Mn and3He enrichments. The Fe/Mn ratio at four sites ranged from about 2 to 9, spanning the average value found for metalliferous sediments (3.5).